‘NATO is Brain-Dead’ : Time For EU Military Force? - He, Wendy (2020)
In terming NATO as “brain-dead”, French President Emmanuel Macron advocated for Europe to develop a military force of its own. More EU leaders have also come out in favour of the idea amid a US in withdrawal mood. Is this the right time for such a move or is this rhetoric at best?